Decree Of The Prime Minister No 377 Of The Year 2014 Amending Prime Ministers Decree No 144 Of The Year 2013 On Establishing A Ministerial Committee For The Project Of The Development Of The Suez Canal Region = قرار رئيس مجلس الوزراء رقم 377 لسنة 2014 بتعديل قرار رئيس الوزراء رقم 144 لسنة 2013 بتشكيل لجنة وزارية لمشروع تنمية قناة السويس - Egypt; The middle east library for economic services, translator. (2025)
Prime Minister Decree No 377 of the year 2014 قرار رئيس مجلس الوزراء رقم 377 لسنة 2014